PENINGKATAN KAPASITAS KEAHLIAN BERWIRAUSAHA DALAM PEMASARAN DIGITAL BAGI WARGA CLUSTER TAMAN HIJAU DESA SINDANGGALIH KARANGPAWITAN GARUT - andhika, Andhika Lungguh Perceka; Anry Sutrisno; Hasbi taobah ramdani (Jurnal Pengabdian Masyarakat DEDIKASI, 2021)
The rapid advancement of technology in various fields requires the public to be able to optimize the function of information technology devices such as gadgets or smartphones in improving the economy. The ease of information from various information media, whether from websites, blogs or social media, allows people to get information and market their products online and more broadly. The purpose of this activity is as a housing model that has utilized Digital as a marketing medium. The extension method used was the Focus Group Discussion (FGD) method which was attended by 40 participants including 35 housewives and 5 young people. The results of the Digital Marketing Workshop are known: as many as 40 residents participated and were interested in knowing more about digital marketing and were enthusiastic about participating in the training. Residents gain knowledge about digital marketing methods through e-commerce websites, social media and are able to identify social media that can be used as marketing media. The conclusion of this activity before attending the Workshop as many as 24 people (55%) did not understand the concept of digital marketing using social media, so that residents had not maximized the use of their gadgets or smartphones for entrepreneurship. After they took part in the training, the knowledge of residents increased, as many as 75% or 32 residents understood the concept of digital marketing, housewives began to use their gadgets to find out how to make processed foods, open accounts on e-commerce websites.